Incidence of Hypertension in the Nepalese Army selected for United Nation's Mission. - Khatri, Devendra; Khatri, Ratna; Yadav, Binita; Rayamajhi, Helina; Rana, Kishor Jung; Pandey, Rajiv (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Hypertension is an important public health challenge in the developing and the developed world alike. However, hospital-based studies on cardiovascular diseases including hypertension in a developing country like Nepal have been limited. The objective of the present study was to determine the incidence of hypertension in the troops selected for mission.Method: We did medical check-up of 850 soldiers selected for UNIFIL mission from January 2014 to March 2014 at Shree Birendra Hospital Chhauni, Kathmandu. Age ranged from 29 years to 55 years was included in the group. Various parameters like history of diabetes mellitus, hypertension, coronary artery disease, smoking, alcohol, family history, measurement of blood pressure, body mass index, lipid profile and number of people who has to take antihypertensive medicines were studied.Results: Out of 850 military personnel 48 found to have high blood pressure. Maximum candidates belonged to young age group 29-35years of age. 22 were overweight and 6 were obese and having higher blood pressure levels. 66% were habituated to alcohol intake minimum 60 ml up to 160 ml. Most of them were occasional drinker. 31 candidates constituting 64.58% had to be put on antihypertensive that were newly diagnosed. 3 persons had past history of hypertension and were already on antihypertensive.Conclusions:  The study highlights the prevalence of various risk factors for coronary artery disease in the army.Since majority of risk factors are modifiable, timely intervention can help in reducing morbidity and mortality.